Global CTEV treatment challenges and adjustments during Covid-19 pandemic: A systematic review - Galuh Nurul Annisa (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Congenital Talipes Equino Varus (CTEV) is a common congenital condition that could lead to lifelong disability. Early intervention using the Ponseti method, a low-cost, highly effective treatment, is essential. However, in the 2020 emerged Covid-19 global pandemic which could impacted on CTEV treatments. Purpose: This study explores the Covid-19 pandemic impact on CTEV treatment and the adaptations developed to ensure continued patient care. Method: A systematic review was conducted according to PRISMA guidelines. Database searches were carried out through screening articles from 2019 to 2023. Results: Out of 23 initial studies, 12 met the inclusion criteria. Covid-19 has caused delays in CTEV treatment globally, reducing access to surgeries, tenotomies, and consultations. Patients faced challenges such as travel restrictions, lack of public transportation, financial strain, and increased travel distances. Healthcare providers dealt with limited resources, clinic closures, and redirected efforts toward Covid-19 care, impacting the availability and frequency of CTEV treatment. These challenges were overcome through telemedicine,